2021
DOI: 10.20873/e12838
|View full text |Cite
|
Sign up to set email alerts
|

Anti-crisis management in Higher Education institutions of Ukraine during the Covid-19 pandemic

Abstract: The article provides an overview of the anti-crisis managerial strategies of the Ministry of Education of Ukraine and educational authorities of Ukrainian higher education institutions in the context of the COVID-19 pandemic. The study comprises results of the on-line survey conducted between the 1st of March 2021 and 11th of April 2021 and covering 380 respondents (faculty members of 12 major higher education institutions in various regions of the country). The statistical and descriptive analysis of the chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Despite these deeply rooted cultural and systemic obstacles, as a whole, Ukraine's universities did manage to respond to the immediate challenges of the pandemic successfully in the short-term (Nenko et al. , 2020, 2021 and Matvienko et al. , 2021).…”
Section: Purpose: Centring On Lived Experience Of Ukraine's Dual Crisesmentioning
confidence: 99%
“…Despite these deeply rooted cultural and systemic obstacles, as a whole, Ukraine's universities did manage to respond to the immediate challenges of the pandemic successfully in the short-term (Nenko et al. , 2020, 2021 and Matvienko et al. , 2021).…”
Section: Purpose: Centring On Lived Experience Of Ukraine's Dual Crisesmentioning
confidence: 99%
“…However, it should be noted that even the most e-learning-ready institutions have shortcomings related to the reduction of direct communication between teachers and students, additional workload on teaching staff, drastic reduction in the number of educational, cultural and sports events, lack of full student life, etc. (Nenko, Orendarchuk, Rudenko, Lytvyn, 2021). Undoubtedly, this is detrimental to effective professional training and education.…”
Section: Challenges In the Education System Duementioning
confidence: 99%
“…The maximum impact on the quality of training occurs if: -the IEE is designed as an open system that integrates intellectual, cultural, program, methodological, organizational and technical resources, -the cybernetic approach is applied to the design and creation of educational, scientific and organizational structures of the IEE, -teachers effectively participate in the formation and filling of the IEE; students are given the opportunity to actively participate in the design of educational trajectories, resource selection, and feedback, -IEE capacity is aimed to develop a set of competencies for future professionals, including soft skills through the implementation of contextual, problembased and developmental learning, -IEE tools ensure the availability of high-quality education and, at the same time, are aimed at ensuring the integrity of training participants (Rakhmanov et al, 2021). The use of information and educational environment in higher education during pandemic threats has confirmed that education policy and response to COV-ID-19 are vital and long-term (Darling-Hammond, Hyler, 2020;Nenko et al, 2021;Wan, 2020). The obtained results testify to the effectiveness of scientific and methodological decisions aimed at technological, psychological and pedagogical, organizational and managerial support of the institution in this difficult time.…”
Section: Practical Suggestions and Recommendations For The Implementa...mentioning
confidence: 99%